2018
DOI: 10.1007/s00018-018-2989-3
|View full text |Cite
|
Sign up to set email alerts
|

Increases in cytosolic Ca2+ induce dynamin- and calcineurin-dependent internalisation of CFTR

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) is a cAMP-regulated, apical anion channel that regulates ion and fluid transport in many epithelia including the airways. We have previously shown that cigarette smoke (CS) exposure to airway epithelia causes a reduction in plasma membrane CFTR expression which correlated with a decrease in airway surface hydration. The effect of CS on CFTR was dependent on an increase in cytosolic Ca 2+ . However, the underlying mechanism fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 66 publications
(78 reference statements)
0
10
0
Order By: Relevance
“…Lack of functional CFTR causes cystic fibrosis lung disease. Acute and chronic cigarette smoke exposures rapidly inhibit CFTR function in smokers and in vitro 124125126. Similarly, e-cigarettes can also inhibit CFTR mediated Cl – secretion and induce airway dehydration in airway epithelia 113.…”
Section: In Vitro Studies Of Vapingmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of functional CFTR causes cystic fibrosis lung disease. Acute and chronic cigarette smoke exposures rapidly inhibit CFTR function in smokers and in vitro 124125126. Similarly, e-cigarettes can also inhibit CFTR mediated Cl – secretion and induce airway dehydration in airway epithelia 113.…”
Section: In Vitro Studies Of Vapingmentioning
confidence: 99%
“…Acute and chronic cigarette smoke exposures rapidly inhibit CFTR function in smokers and in vitro. 124 125 126 Similarly, e-cigarettes can also inhibit CFTR mediated Cl – secretion and induce airway dehydration in airway epithelia. 113 Failure of ciliary beating induced by e-cigarette aerosol could conflate this, contributing to a retention of mucus and bacteria, increasing the chance of developing lung disease ( table 2 ).…”
Section: In Vitro Studies Of Vapingmentioning
confidence: 99%
“…Low temperature incubation rescues CFTR in F508del-expressing cells (r.F508del) (Denning et al, 1992), but the protein still demonstrates reduced stability and is rapidly removed by peripheral quality control mechanisms (Okiyoneda et al, 2010). In fact, environmental stresses may also lead to destabilization and internalization of WT-CFTR (Bomberger et al, 2012;Patel et al, 2019). Stabilizers are agents that anchor CFTR at the PM, thus preventing its removal and degradation by lysosomes (Fukuda and Okiyoneda, 2018).…”
Section: Stabilizers: Rescuing the Protein Stability At The Plasma Mementioning
confidence: 99%
“…1; Garcia -Arcos et al 2016;Chung et al 2019;Lin et al 2019). Whilst the mechanism of nicotine-dependent CFTR inhibition is not fully understood, we have previously found that CFTR is inhibited by elevations in cytoplasmic Ca 2+ (Rasmussen et al 2014;Patel et al 2019). This causes CFTR dephosphorylation (Marklew et al 2019), and we speculate that nicotine-dependent Ca 2+ influx through nAChRs likely inhibits CFTR through a similar process, indicating a mechanistic link between nicotine intake and epithelial ion channel dysfunction.…”
Section: The Effects Of Nicotine On the Lungmentioning
confidence: 83%